Ethno-science Approach in Making Bamboo Lemang Materials: Implications of Understanding the Concept of Thermal Energy - Walid, Ahmad; Yunilarosi, Elvida Sari; Agustina, Rahma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the influence of ethno-science approach through the making of bamboo lemang in improving students' understanding of the concept of thermal energy material at SMPN 17 South Bengkulu. This study uses a quantitative approach with a quasi-experiment method and a Non-Equivalent Control Group design. Creswell states that a pseudo-experiment is an experimental situation in which the researcher assigns, but not randomly, participants to a group because the researcher cannot artificially create a group for the experiment. Data were collected through concept comprehension tests and observations. The results of the study showed a significant improvement in the understanding of students who used the ethno-science approach compared to conventional methods. Based on the results of the normality test with Shapiro-Wilk, it showed a significance value of 0.129 (experimental class) and 0.067 (control class), which means that the data is normally distributed. Based on the results of the homogeneity test with Levene's Test resulting in a significance value of 0.611, indicating that the data variance between the experimental and control groups was homogeneous. Based on the results of the hypothesis test using Independent Samples t-Test, it showed a t-value (-5.42) with p = 0.000, which means that there was a significant difference between the two groups. The average understanding of students in the experimental class was 83.07, while in the control class it was 66.13.These results show that the ethno-science approach through the making of bamboo lemang contributes positively to improving the understanding of the concept of thermal energy.Keywords: Ethno-science, Bamboo Lemang and Heat energy